Starch adulteration in turmeric samples through multivariate analysis with infrared spectroscopy. (15th March 2021) - Macêdo, Isaac Yves Lopes de; Machado, Fabio Bahls; Ramos, Gabrielle Santos; Costa, André Gabriel do Carmo; Batista, Rayssa Dias; Filho, Arlindo Rodrigues Galvão; Asquieri, Eduardo Ramirez; Souza, Aparecido Ribeiro de; Oliveira, Anselmo Elcana de; Gil, Eric de Souza
Highlights: Starch content of turmeric samples influences the spectroscopic data. Turmeric samples can classified by adulteration with K-means of infrared spectra. Electroanalysis show potentially lesser antioxidant capacity in adulterated samples. 50.48 g starch per 100 g turmeric is the found threshold for adulteration. Partial least squares regression determined starch content of turmeric.